PENYULUHAN TENTANG PREEKLAMSIA PADA KEHAMILAN DI WILAYAH KERJA PUSKESMAS SIMPANG TIGA KABUPATEN ACEH BESAR - Martina; Zuhkrina, Yuli; Marjunita; Nurlaila; Sastika, Omi; Zulbaini; Hastuti, Dewi (PORTAL RISET DAN INOVASI PENGABDIAN MASYARAKAT, 2021)
In Indonesia, bleeding, hypertension in pregnancy, and infection continue to be the three leading causes of death among mothers. However, the proportion has changed, where bleeding and infection tend to decrease while the proportion of HDK (preeclampsia and eclampsia) is increasing. WHO estimates that cases of preeclampsia are seven times higher in developing countries than in developed countries. The prevalence of preeclampsia in developed countries is 1.3%-6%, while in developing countries it is 1.8%-18%. The incidence of preeclampsia in Indonesia alone is 128,273/year or about 5.3%. Based on data from the Indonesia Health Profile in 2017, bleeding is said to be the highest cause of maternal death in Indonesia (30,3%), then preeclampsia (27,1%), due to infection by 7,3% and other causes. preeclampsia is a hypertensive disorder in pregnancy which is also accompanied by proteinuria. In Indonesia, preeclampsia is currently the second highest cause of maternal death after bleeding. More than 4 million pregnant women experience preeclampsia each year. It is estimated that every year 50.000 to 70.000 women die from preeclampsia and 500.000 babies die. Preeclampsia is the cause of 15-20% of maternal deaths worldwide and the leading cause of fetal mortality and morbidity. The method used is Pre Test and Post Test using a questionnaire. Based on the results of the counseling there was an increase in respondents' knowledge about preeclampsia, which was in the good category as much as44 (93,6%). In conclusion, there is a very significant increase in respondents' knowledge after being given counseling.